STATUS OF PHYSICAL CAPACITY OF LOWER SECONDARY EDUCATION STUDENTS - M. Tzankova-Kaloyanova (Trakia Journal of Sciences)
The status of the physical capacity of students is a very accurate and objective indicator, through which the efficiency of the educational process in physical education and sports can be assessed. The aim of this research is to determine the current state of the physical capacity among the students from V to VII grade from Secondary School “D. Debelyanov”, Burgas. The study was conducted with 156 students, who were divided into two groups – boys and girls. Indicators of the physical capacity of students are their physical achievements. In order to define those, tests have been applied, taken from the new system for assessing the physical capacity of students. A test battery was used, which includes the following indicators – running (sprint) 30m from a high (standing) start, long jump from a standing point, throwing a thick 3 kg ball with two hands over head, running 200 m, T-test (agility). The results of the study are processed mathematically and statistically by applying comparative analysis, Student's t-test, variation analysis. The average grades of the surveyed students from 5th to 7th grade, according to the studied indicators, fall into the range of the “Good” score (in 20-level scoring), for both sexes. Only on the indicator №3 (Throwing a thick ball 3 kg) among the girls of 5th class, the grade is “Average”. In this age group, it is recommended to use tools and techniques in order to develop the strength of the upper limbs and of the abdominal muscles.